Factors Influencing Seniors’ Anxiety in Using ICT - Mike Reid; Torgeir Aleti; Bernardo Figueiredo; Jacob Sheahan; Larissa Hjorth; Diane M. Martin; Mark Buschgens (Social Sciences)
The ability of older adults to engage with information and communication technologies (ICT) is crucial in today’s more digital and connected world. Anxiety about and failure to adopt and engage with ICT is increasingly likely to be a barrier in daily living for older adults, potentially reducing their freedom as consumers, quality of life, independence, and wellbeing. It may also be a significant factor in social and economic exclusion. Drawing on consumer behaviour, ICT theories and frameworks, and a quantitative survey of 706 older Australian adults, this paper examines factors influencing anxiety in engaging with ICT. Our findings show that perceived anxiety was associated with increased subjective norms or when others placed pressure on older people to engage more with ICT and when older adults perceived increased risks associated with ICT engagement. Conversely, reduced levels of perceived anxiety were correlated with a positive attitude towards ICT and when older people had the technical and cognitive resources to adopt and engage with ICT. The results highlight the importance of building, renewing, and reinforcing digital competencies in older consumers. Understanding factors associated with ICT-related anxiety means that organisations will be better placed to develop campaigns, products, programmes, and policies for older consumers that actively reduce anxiety, increase their use of ICT, and reduce the digital divide.